2010
DOI: 10.1002/pbc.22778
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐emetic effect of ginger powder versus placebo as an add‐on therapy in children and young adults receiving high emetogenic chemotherapy

Abstract: Ginger root powder was effective in reducing severity of acute and delayed CINV as additional therapy to ondensetron and dexamethasone in patients receiving high emetogenic chemotherapy (ClinicalTrials.gov identifier: NCT00940368).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 14 publications
1
113
1
1
Order By: Relevance
“…Participants with body weight between 20 and 40 kg received 1 g/day ginger (6 capsules of 167 mg ginger) or matching placebo from day 1 to day 3 of chemotherapy. Patients with body weight between 40 and 60 kg took 2 g/day ginger (5 capsules of 400 mg ginger) or matching placebo from day 1 to day 3 of chemotherapy [21]. In another study, ginger at doses of 0.5 and 1 g per day significantly reduced CIN as add-on to standard antiemetic regimens.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Participants with body weight between 20 and 40 kg received 1 g/day ginger (6 capsules of 167 mg ginger) or matching placebo from day 1 to day 3 of chemotherapy. Patients with body weight between 40 and 60 kg took 2 g/day ginger (5 capsules of 400 mg ginger) or matching placebo from day 1 to day 3 of chemotherapy [21]. In another study, ginger at doses of 0.5 and 1 g per day significantly reduced CIN as add-on to standard antiemetic regimens.…”
Section: Discussionmentioning
confidence: 95%
“…Three independent study groups have investigated the effect of ginger on prevention of CINV [20][21][22]. The results of Sontakke et al study showed that ginger is as effective as metoclopramide in reducing CINV.…”
Section: Discussionmentioning
confidence: 99%
“…The most thoroughly research supplement is ginger as clinical trials have been conducted in both adults and children with cancer. A double-blind, placebocontrolled, randomized trial among 32 children and young adults with newly diagnosed bone sarcomas evaluated the ef fi cacy of ginger as an adjunct to the standard of care (Pillai et al 2011 ) . Children and young adults between the ages of 8-21 were randomized to receive ginger powder (1,000-2,000 mg/day) or placebo for fi ve days at the beginning of a chemotherapy cycle and for 2 days post in addition to the standard of care.…”
Section: Nausea and Vomitingmentioning
confidence: 99%
“…A new trial is planned starting with the adult information, which showed a CINV rate ranging from 30% to 90%. 19 If a relative reduction in the rate of CINV of 20% is considered clinically relevant (this is another assumption, which may vary because the participants are children rather than adults), and a type I error of .05 and power of 80% is assumed, the sample size calculation will depend greatly on the control event rate. If a control event rate of 60% is assumed (approximately the middle of the 30%-90% range found in adults), then a new trial would require at least 267 patients in each arm.…”
Section: Examplementioning
confidence: 99%